Chemical characteristic and cholesterol level of local sheep with intensive fattening. (March 2019) - Hatta, Muhammad; Priyanto, Rudy; Mas, Muhammad Sayuti; Prahesti, Kusumandari Indah
Abstract: Red meat is a livestock product with high nutrition. Red meat obtained from sheep had high fat and cholesterol content. Fat and cholesterol in the body of livestock could be reduced by feed manipulation through the gastrointestinal system approach. This research was aimed to examine the effect of feed containing shrimp waste on unsaturated fat and fatty acids, blood cholesterol, internal fat, and subcutaneous fat of local sheep in Bogor. The research was designed using Completely Randomized Design with four feed formulas as the treatments of four replicates. Sheep were slaughtered after being kept in individual cages for 3 months. Further, the percentage of internal fat, total cholesterol, triglycerides, HDL and LDL in the blood were analyzed. The parameters measured were the percentage of internal fat and the iodine number of subcutaneous fat, total cholesterol, triglycerides, HDL and LDL level in the blood. The results showed that the higher percentage of shrimp waste reduced blood cholesterol, triglycerides, and LDL level and increased blood HDL level and iodine number (unsaturated fat) of lamb meat.